Human Prothrombin - Derleth, Th. R; Penner, J. A (Thrombosis and Haemostasis, 1970)
A method is presented for the chromatographic separation of human prothrombin from variable volumes of plasma. The procedure is simple, consisting of chromatography on ECTEOLA which provides a potent product containing factor IX and X activity sufficient for therapeutic use. Additional chromatography on DEAE or Sephadex G200 will produce a prothrombin of high specific activity which appears homogeneous by ultracentrifugation and electrophoresis on cellulose acetate, although multiple protein fractions can be identified on starch gel electrophoresis.Human prothrombin prepared by this method migrates as an alpha 2-globulin and does not appear to be altered electrophoretically or antigenically from its original state in the plasma. The characteristics of human prothrombin obtained from patients with deficiencies of factor VII or IX do not differ from normal.